Advanced assembly language - Holzner, Steven (Peter Norton programming library, 1991)
A utility for writing working assembly language programs using assembler software. The text provides a functional approach covering keyboard, screen handling, and file handling among other topics. The disk contains over one hundred ready-to-run programs. Assumes the user has some assembly language background.